ANALYSIS ON RELATIONSHIP BETWEEN LEADERSHIP STYLE AND EMPLOYEE MOTIVATION IN CHURCH ORGANIZATION AT GMIM SOUTH MANADO AREA - Tumbel, Brilliany C. (Sam Ratulangi University, 2016)
Motivation is an internal force to satisfy the need and to accomplish specific goals, while leadership is the process of influencing others to understand and agree about what needs to be done and how to do it, and the process of facilitating individual and collective efforts to accomplish shared objectives. This study aims to learn and observe the connection between Leadership Style and Employee Motivation which in this case at Church Organization in GMIM South Manado Area. This research is a quantitative research associated with simple regression analysis technique. The respondents of this research are the employees working at the Churches in South Manado Area with total 32 people. The results show there is a significant relationship between Leadership Style and Employee Motivation. It concluded that way the leaders treat the employee is really important and does influenced the employee motivation to work and directly affected the working performances.